Politics, water management and infrastructure. (3rd April 2020) - Trowsdale, Sam; Boyle, Kelly; Baker, Tom
Abstract : While modern water management has been central to the achievement of a range of beneficial social outcomes, it has increasingly drawn criticism for its disconnection from democratic decision-making, hindering efforts to develop more resilient systems. This paper examines how an experiment with more resilient water infrastructure politicized centralized water management focusing, in particular, on a stormwater re-use 'third-pipe' system at a large residential development in Auckland, New Zealand. Through analysis of resident and expert views on safety, cost and security, the paper attends (1) to the ways in which techno-managerial water management was contested and, thus, politicized through the implementation of the third pipe, and (2) how the mobilization of techno-managerial discourses by water management authorities delegitimized the third-pipe system, rendering it ultimately inoperable. While our case study was thwarted by the de-politicizing apparatus of water management authorities, such experiments offer precedents, resources and hope for more democratic systems of water management. This article is part of the theme issue 'Urban flood resilience'.